2020
DOI: 10.1111/dth.14054
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of ustekinumab in patients with hidradenitis suppurativa using intravenous induction

Abstract: Hidradenitis suppurativa (HS) is a chronic, systemic, inflammatory dermatosis which lacks curative treatment. Its management can be challenging, thus a variety of therapies are commonly used, such as antibiotics, anti-inflammatory drugs, retinoids, surgery and biological treatments. Adalimumab is the only approved biological therapy for HS, while secukinumab, risankizumab or guselkumab are currently under investigation with ongoing trials for HS. 1,2 To our knowledge, there are currently no clinical trials bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…DLQI and VAS of pain improved by ≥30% in 71.42% of patients in the absence of significant ustekinumab-related side effects [ 241 ]. In accordance with these findings, Sánchez-Martínez and colleagues, evaluating the effectiveness and safety of the ustekinumab dosing schedule approved for CD in 6 adalimumab-experienced HS patients (50% female), found that 50% of patients achieved HiSCR at week 12, without any drug-related side effects [ 242 ]. Rather recently, Scholl et al also reported the potential utility of a high-dose regimen of ustekinumab in their case series including 3 biologic-experienced HS patients (1 female and 2 males) [ 243 ].…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 71%
“…DLQI and VAS of pain improved by ≥30% in 71.42% of patients in the absence of significant ustekinumab-related side effects [ 241 ]. In accordance with these findings, Sánchez-Martínez and colleagues, evaluating the effectiveness and safety of the ustekinumab dosing schedule approved for CD in 6 adalimumab-experienced HS patients (50% female), found that 50% of patients achieved HiSCR at week 12, without any drug-related side effects [ 242 ]. Rather recently, Scholl et al also reported the potential utility of a high-dose regimen of ustekinumab in their case series including 3 biologic-experienced HS patients (1 female and 2 males) [ 243 ].…”
Section: (New Medical) Therapeutical Approaches In Hsmentioning
confidence: 71%
“… 89 Furthermore, real-life observations support that it can be effectively and safely used in patients who develop paradoxical psoriasis while receiving anti-TNF-α treatment, 51 as well as for the treatment of hidradenitis suppurativa. 90 Safety profile and efficacy on extraintestinal manifestations also advocate in favor of ustekinumab as a reasonable candidate for the combination of targeted therapies, for patients with medical-refractory IBD without other medical options as well as for those with concomitant IBD and extraintestinal manifestations. 91 , 92 Moreover, unlike with anti-TNF-α drugs, treatment with ustekinumab is associated with a more durable efficacy over time, mainly due to its low rate of immunogenicity.…”
Section: Methodsmentioning
confidence: 99%
“…173 A retrospective study including six patients treated with this regime obtained the same clinical response. 174 Moreover, in a retrospective study, HiSCR was achieved by 9/10 patients treated with UST 90 mg every 8 weeks (without induction dose). 175 Whether higher doses are more effective in HS requires further evaluation in RCTs.…”
Section: Treatmentmentioning
confidence: 99%